2022
DOI: 10.1038/s41467-022-33210-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and biological study of fusion genes as resistance mechanisms to EGFR inhibitors

Abstract: The clinical significance of gene fusions detected by DNA-based next generation sequencing remains unclear as resistance mechanisms to EGFR tyrosine kinase inhibitors in EGFR mutant non-small cell lung cancer. By studying EGFR inhibitor-resistant patients treated with a combination of an EGFR inhibitor and a drug targeting the putative resistance-causing fusion oncogene, we identify patients who benefit and those who do not from this treatment approach. Through evaluation including RNA-seq of potential drug re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In an effort to conduct a detailed functional analysis of SSCVs, we established CRISPR genome editing models derived from PC-9 46,47 , a lung cancer cell line, for each SSCV (c.5048-132G>C and c.5048-132G>T). We successfully introduced the NOTCH1 deep intronic SSCV into the cell line, confirming a 129 bp exon extension (Figure 6c, Supplementary Figure 20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to conduct a detailed functional analysis of SSCVs, we established CRISPR genome editing models derived from PC-9 46,47 , a lung cancer cell line, for each SSCV (c.5048-132G>C and c.5048-132G>T). We successfully introduced the NOTCH1 deep intronic SSCV into the cell line, confirming a 129 bp exon extension (Figure 6c, Supplementary Figure 20).…”
Section: Resultsmentioning
confidence: 99%
“…NOTCH1 SSCVs (c.5048-132G>C, c.5048-132G>T) were created in the PC-9 cell lines as previously reported 46,47 . We designed sgRNA and donor templates for CRISPR-Cas9 homology directed repair (HDR) using Alt-R HDR Design Tool (Integrated DNA Technologies, IDT).…”
Section: Investigation Of Positional Relationship Between Splice-site...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kobayashi et al conducted a comprehensive study on fusion genes and their role in mediating resistance to EGFR TKIs in EGFR- mutant lung cancer. 12 Specifically, they identified that only a minority of detected fusion genes, such as CCDC6-RET , are functional and capable of imparting resistance to EGFR inhibitors. In a brief review, Zhao et al reported that the co-occurrence of EGFR mutations and RET fusions in patients with EGFR -mutant NSCLC is predominantly induced by osimertinib, a third-generation EGFR-TKI.…”
Section: Discussionmentioning
confidence: 99%
“…1). Inspired by the recent reports indicating fusion oncogene formation as a mechanism of resistance to EGFR inhibitors 7,20,21 , we applied FACTS into the in vitro model of EGFR inhibitor resistance using PC-9 cells, harboring EGFRactivating mutation (EGFR E746-A750del) 22 .…”
Section: Characterization Of Kinase Fusions Across Cancer Typesmentioning
confidence: 99%